Living on the edge: Effects of body size, group density and microhabitat selection on escape behaviour of southern leopard frogs Lithobates sphenocephalus - Bateman, Bill; Fleming, P. (Current Zoology Editorial Office, 2014)
Models of optimal escape strategy predict that animals should move away when the costs of fleeing (metabolic and opportunity costs) are outweighed by the costs of remaining. These theoretical models predict that more vulnerable individuals should be more reactive, moving away when an approaching threat is further away. We tested whether escape behaviour (including ‘escape calling’) of Lithobates sphenocephalus approached by a human was influenced by body size or the initial microhabitat that the individual was found in. Irrespective of their size, frogs in the open tended to remain immobile, enhancing their crypsis. Frogs in cover showed different responses according to their body size, but, contrary to our initial predictions, larger frogs showed greater responsiveness (longer flight initiation distance and distances fled) than small frogs. Small frogs tended to remain closer to water and escaped into water, while larger individuals were more likely to jump to terrestrial cover and call during escape. Density of frogs near the focal animal had no effect on escape behaviour. This study indicates a range of escape responses in this species and points to the importance of divergent escape choices for organisms which live on the edge of different environments [Current Zoology 60 (6): 712–718, 2014].